Relationship between Multiple Intelligences and Reading Proficiency of Iranian EFL Students. - Hajhashemi, Karim (2010)
The purpose of this study was to examine the relationship between multiple intelligences (MI) and reading proficiency of Iranian EFL pre-university students in Tehran, Iran and to see if gender plays a role in this regard. Specifically, the study attempted 1) to verify the intelligences identifiable among high/low achievers in reading, 2) to discover the differences in multiple intelligences of Iranian EFL students based on their reading proficiency and gender, 3) to determine the relationship between the multiple intelligences and reading proficiency of Iranian EFL students, 4) to identify the components of multiple intelligences which are correlated with the score of reading proficiency test of Iranian EFL students, and 5) to find the intelligence type that is the best predictor of learners‟ performance in reading proficiency test. In order to meet the objectives, four research questions were asked. A descriptive and ex post facto design was employed to ascertain relationships among the naturally occurring variables. The participants for this study were 128 pre-university students (grade12, 18-19 years old) of both genders studying in Tehran in the academic year 2008-2009. The district was chosen randomly among 19 school districts of Tehran. The students were chosen randomly from two different segregated high schools in that region. Random sampling was used to create homogeneous groups without involving any potential biases or judgments. Three instruments were utilized in this study namely, 1) a demographic questionnaire; 2) the Persian version of McKenzie‟s MI Inventory; and 3) a standardized reading proficiency test which was selected from retrieved paper-based TOEFL® tests. Analyzing the data using t-test, it was found that there was a statistically significant difference in the mean musical-rhythmic intelligence scores of the low achievers and the high achievers. This means that there were no significant differences between intelligence types of the students and their reading proficiency scores except for their musical-rhythmic intelligence which was positive and stronger among the low achievers. Based on this, it seems that the high achievers have a lower musical intelligence, which also means that better readers are less intelligent „musically‟. A statistically significant difference between the mean bodily-kinesthetic intelligence scores and the two genders was also revealed. In other words, no significant gender difference was found in the intelligence types of the students except their bodily-kinesthetic intelligence which was positive and stronger among the females. No significant difference was found between the male and female Iranian EFL pre-university students in their reading proficiency scores. Results obtained from the correlation analysis revealed no significant relationship between the two variables of MI and reading score. Based on Guilford‟s rule of the thumb, the relationship of MI and reading scores in the present study was found to be negligible. Furthermore, the results of the correlation analysis revealed that there was a low significant, negative relationship between musical-rhythmic intelligence and reading which suggests that when the reading score of a student increases, musical-rhythmic intelligence of the same student decreases and vice versa. This finding indicates that the low proficiency EFL learners‟ reading comprehension performance is related to the musical-rhythmic intelligence. Overall, three categories of MI were found to be predictive of reading proficiency. Those significant predictor variables were musical-rhythmic, verbal-linguistic, and bodily-kinesthetic intelligences. The coefficient of determination R² of the variables (musical-rhythmic, verbal-linguistic, and bodily-kinesthetic) showed that these variables contributed 13.5% of the variance in reading proficiency collectively.